Navigating, challenging, and contesting normative gendered discourses surrounding women’s pornography use - Marques, Olga (Journal of Gender Studies, 2019)
While there exists some empirical research on women’s use of pornography, the manner in which women do, and how they understand their pornographic spectatorship, remains under-examined. Focusing on the narratives of 26 women gained through both focus groups and individual interviews, this research explores how women who use pornography and other sexually explicit materials navigate, reaffirm, challenge, and contest normative gendered boundaries that surround women’s sexuality, sexual pleasure, and women’s pornographic use. While ‘pornography as female degradation’ is the most visible feminist discourse, the findings of this study suggest that the meanings attributed to both the experience of engaging with pornography, as well as with pornographic materials themselves, were far from wholly degrading, and in fact, served to provide pleasure, sexual self-actualization, and even corporeal validation – disrupting normative discourses of desiring and desirable bodies.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; corps; cours; féminisme pop; ontario; premier cycle; périodes historiques; régions géographiques; sex1911; sexualité; thématiques